Screening for Antibacterial and Antifungal Activity in Fungi Associated with Molluscs - Lumban Gaol, Josua Gabriel; Pringgenies, Delianis; Ari Setyati , Wilis (Jurnal Moluska Indonesia, 2025)
Molluscs are invertebrate organisms that produce secondary metabolites to adapt to their environment. These secondary metabolites are also found in fungi that live in symbiosis with molluscs. Research has shown that these symbiotic fungi produce various secondary metabolites with antibacterial and antifungal properties. This study aims to explore the potential of fungi associated with molluscs in developing bioprospecting strategies against pathogenic bacteria and fungi. The antibacterial and antifungal screening tests were conducted against the pathogenic bacteria Escherichia coli and Staphylococcus aureus, and the pathogenic fungi Candida albicans and Trichoderma harzianum, over a period of 36 hours. The results indicated that 12 isolates of mollusk-associated fungi exhibited antibacterial activity against the tested bacterial pathogens. Additionally, 4 of these 12 isolates also demonstrated antifungal activity. The antibacterial and antifungal activities were identified by the clear zones formed in the test medium. The screening tests revealed that fungi associated with molluscs possess antibacterial and antifungal activities against several tested pathogenic bacteria and fungi. Keywords: Pathogenic Bacteria; Association Fungi; Pathogenic Fungi; Molluscs